J. Whitley, Knossos. Myth, History and Archaeology. - Driessen , Jan (Journal of Greek Archaeology, 2024)
This account of the history of Knossos forms part of a wider series of Archaeological Histories that discusses the history of sites, buildings and towns from their construction to the present day and it is in this context that Whitley’s pleasantly written – with a style somewhere between the academic and the personal – and instructive book should be approached. Knossos, or rather its studies, are very much alive. It not only forms the core of two other, recently published books on Minoan civilization,1 and even after the completion of this book in 2021, new studies have appeared on some of the Knossos remains, not included in this account (Oddo 2022; Knappett et al. 2023).